Clinical-Pathological Analysis of 37 Oral Squamous Cell Carcinomas in Tucumán, Northwestern Province of Argentina: Immunohistochemical Study of p53 In Selected Cases - Blunda, S. (2024)
Oral squamous cell carcinoma (OSCC) represents 3% of all malignant neoplasms. Considering the bserved regional occurrence of OSCC, the aim of this study was to analyze the incidence and clinical characteristics of patients with primary carcinoma of the oral cavity diagnosed in the province of Tucumán, in the Northwestern of Argentina, where habits and lifestyle can play a central role in its incidence. A cross-sectional, descriptive and exploratory study was conducted with 37 clinical records of patients with OSCC. The study included the analysis of clinical and histological parameters, risk factors and the presence of p53 mutations in relation to the histopathological grade and the carcinoma in situ (CIS) component. OSCC is the most frequent oral malignancy in Tucumán. Most of the patients (81.1%) were male, and the mean age range was 65.5 years. The analysis of risk factors showed that 89.2% of the patients smoked. Most of the tumors (38%) were located on the tongue and the greater histological aggressiveness of OSCC was observed in this location. Overexpression of p53 was observed in OSCC with CIS component. OSCC is the most frequent oral malignancy in Tucumán. The data also agree with reports from other locations in terms of sex, age, location, and greater histological aggressiveness of OSCC in the tongue. The overexpression of p53 in OSCC with a CIS component could indicate the occurrence of its mutation in early lesions. The mutation in p53 in non-invasive lesions found in the adjacent surface epithelium could have predictive potential for progression or recurrences from inadequate surgical margins.